Analisis Potensi Longsor Kecamatan Samigaluh, Kabupaten Kulonprogo, DIY, Menggunakan Perbandingan Metode Analitycal Hierarchy Process (AHP) Dan Weighted Linear Combination (WLC) - Adam Nurapriyana AMNO; Bernadeta Subandini Astuti (Retii, 2023)
One of the areas that is a landslide hotspot in Indonesia is Samigaluh District, Kulonprogo Regency, Yogyakarta Special Region. This research aims to conduct studies or research from previous researchers regarding the potential for landslides and map the distribution of areas prone to landslides and the parameters that influence the potential for landslides using a comparison between the Analytical Hierarchy Process (AHP) method and the Weighted Linear Combination (WLC) method with using the same parameters, which are considered to influence the level of vulnerability to landslides. In this research, there are several stages or methods that are followed, including the preparation stage, data collection stage, data analysis stage, final stage & report preparation. Based on the results of the analysis of weighting and standardization of values ​​and making a comparison between the AHP method and the WLC method in the research area in Samigaluh District, Kulonprogo Regency, Special Region of Yogyakarta based on the results of calculations using the comparison and overlay matrix method, it was found that in the AHP method the landslide prone areas were divided into 3 danger index, namely low danger (1906 Ha), medium danger (1835 Ha), and high danger (3062 Ha). Meanwhile, in the WLC method, landslide-prone areas are divided into 2 hazard indices, namely medium hazard (339 Ha) and high hazard (6429 Ha). In both methods, the parameter that influences or dominates is the very steep slope. The results of field validation also show that the research area is a class landslide-prone area, which is found on the landslide-prone area (KRB) map that has been created.